PREDIKSI PROFIT PERUSAHAAN DENGAN KLASIFIKASI ALGORITMA C4.5 PADA PT TUNAS JASA MANDIRI - Michael Jordan; Saragih, Saut (Computer Science and Industrial Engineering, 2022)
The development of technology and information has brought changes in all fields, including the development of the business world. The dynamic development of technology and information accompanied by the times can produce fast and accurate information and does not require a long time to find the information needed. It is undeniable that the rapid development of technology and information is currently attracting the attention of the wider community, including companies that manage industrial estates where business activities always require significant calculations of information to carry out a business plan that they manage every year. PT Tunas Jasa Mandiri is a subsidiary of PT Tritunas Bangun Perkasa which manages the Tunas industrial area. PT Tunas Jasa Mandiri was established in 2008 which is located on Jl. Raja Isa - Tunas Ruko Industrial Estate Blok 1A No. 10 Batam Center. So far, the company has a collection of data related to the achievement of company performance that has cost a lot of money but the data has not been used properly. Through the application of data mining technology with the C4.5 algorithm, a set of untapped transaction data will be processed and produce new knowledge which becomes something valuable and useful for companies, especially in predicting profit achievement